Pengendalian Kualitas Produk Cacat Jumbo Bag Menggunakan Siklus Pdca (Plan-Do-Check-Act) di PT. XYZ - Dian Rahma Aulia; Hery Murnawan (Asosiasi Riset Ilmu Manajemen dan Bisnis Indonesia, 2024)
PT. XYZ, a plastic bag packaging industry, is still facing poor quality problems and a high level of malfunction. The sewing and printing sectors are the biggest contributors to defects in the production of Jumbo Bag. The objective of this research is to identify the causes of dominant defects, provide repair solutions, and reduce product defects, as well as decrease the value of defects per unit of dominating defects. To solve this problem, the researchers used the plan-do-check-action method (PDCA). The PDCA method is used to identify and address defects, while the 5W1H is used for identifying the cause of defects and developing corrective solutions. Using this method, PT. XYZ can reduce product defects and improve the quality of the Jumbo Bag. The result is a reduction in defects per unit of wrong sewing defect from 0.014 DPU to 0.005 DPU, accessory deficiency defects from 0.008 DPU to 0.04 DPU, hole defects of 0.007 DPU to 0.001 DPU, and printing defects from 0.004 DPU to 0.044 DPU. Thus, the company can improve product quality and meet customer expectations.